Tongue Flap Reconstruction in Carcinoma of Oral Cavity: An Institutional Experience - Kumar, Vijay (J Maxillofac Oral Surg, 2018)
INTRODUCTION: Abundant blood supply of tongue permits various flap designs and makes it a good choice for reconstructing defects following resection of oral cancer. AIM: We aim to evaluate the reliability of tongue flap for small- and medium-size defects after resection of oral cancer in terms of viability, complications, and functional outcome. METHODS: In this retrospective analysis, patients reconstructed with lateral tongue flaps after resection of oral cavity carcinoma from May 2011 to December 2017 were included. RESULTS: Forty-two patients underwent tongue flap reconstruction during the study period. Median size of defect was 3.5 cm. Out of 42 patients, 27 had carcinoma of buccal mucosa and 8 had carcinoma of lower alveolus. Mandibular resection was performed in 30 patients. Neck was addressed in all 42 patients. Supraomohyoid neck dissection was done in 12 patients, while others had comprehensive neck dissection. Average time to harvest flap was 25 min. There was no flap loss in the postoperative period. Three patients each developed flap tip necrosis and minor orocutaneous fistula that were managed conservatively. Subjective functional outcome was good to satisfactory in most patients (88%). CONCLUSION: Lateral tongue flap is a simple reliable flap for reconstruction of small- and medium-sized defects following resection of oral cavity cancers in terms of low morbidity and satisfactory functional outcomes. It obviates the need of distant tissue transfer.